"I train and mentor, they take them": A qualitative study of nurses' perspectives of neonatal nursing expertise and its development in Kenyan hospitals - Mary Nyikuri; Pratap Kumar; Mike English; Caroline Jones (Wiley, 2020)
Abstract Aims and Objectives Neonatal inpatient care is reliant on experienced nursing care, yet little is known about how Kenyan hospitals foster the development of newborn nursing experience in newborn units. Design A Qualitative ethnographic design. Methods Face to face 29 in depth interviews were conducted with nurses providing neonatal care in one private, one faith based and one public hospital in Nairobi, Kenya between January 2017 and March 2018. All data were transcribed verbatim, coded in the original language and analysed using a framework approach. Results Across the sectors, nurses perceived experience as important to the provision of quality care. They noted that hospitals could foster experience through recruitment, orientation, continuous learning and retention. However, while the private hospital facilitated experience building the public and faith‐based hospitals experienced challenges due to human resource management practices and nursing shortages. Conclusion Health sector context influenced how experience was developed among nurses. Implications Nurturing experience will require that different health sectors adopt better recruitment for people interested in NBU work, better orientation and fewer rotations even without specialist nurse training.